2014
DOI: 10.1155/2014/135048
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Effects of Saffron-Derived Carotenoids in Prostate Cancer Cell Models

Abstract: Crocus sativus L. extracts (saffron) are rich in carotenoids. Preclinical studies have shown that dietary intake of carotenoids has antitumor effects suggesting their potential preventive and/or therapeutic roles. We have recently reported that saffron (SE) and crocin (CR) exhibit anticancer activity by promoting cell cycle arrest in prostate cancer (PCa) cells. It has also been demonstrated that crocetin esters are produced after SE gastrointestinal digestion by CR hydrolysis. The aim of the present report wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(70 citation statements)
references
References 34 publications
3
67
0
Order By: Relevance
“…N = 5, each value represents mean ± SD, *p < 0.05 versus the NC mimic group. GAPDH: glyceraldehyde 3-phosphate dehydrogenase; HIF-1α: hypoxia-inducible factor-1α; KLF5: Krüppel-like factor 5; miR: microRNA; mut: mutant; NC: negative control; mRNA: messenger RNA; PCR: polymerase chain reaction; SD: standard deviation; wt: wild-type Evidence has accumulated that crocin has anticancer activities in many cancers (Festuccia et al, 2014;Hire et al, 2017;Mollaei et al, 2017). Its effect in gastric cancer is not fully understood, although a previous study found that it could trigger apoptosis of gastric adenocarcinoma AGS cells by increasing the Bax/Bcl-2 ratio (Hoshyar et al, 2013).…”
Section: Crocin Modulates Klf5 Expression By Elevating Mir-320 Exprmentioning
confidence: 99%
“…N = 5, each value represents mean ± SD, *p < 0.05 versus the NC mimic group. GAPDH: glyceraldehyde 3-phosphate dehydrogenase; HIF-1α: hypoxia-inducible factor-1α; KLF5: Krüppel-like factor 5; miR: microRNA; mut: mutant; NC: negative control; mRNA: messenger RNA; PCR: polymerase chain reaction; SD: standard deviation; wt: wild-type Evidence has accumulated that crocin has anticancer activities in many cancers (Festuccia et al, 2014;Hire et al, 2017;Mollaei et al, 2017). Its effect in gastric cancer is not fully understood, although a previous study found that it could trigger apoptosis of gastric adenocarcinoma AGS cells by increasing the Bax/Bcl-2 ratio (Hoshyar et al, 2013).…”
Section: Crocin Modulates Klf5 Expression By Elevating Mir-320 Exprmentioning
confidence: 99%
“…Crocin inhibits tumor growth and its spread in several forms of cancer including colorectal7, pancreatic89, breast10, and prostate cancers11, as well as chronic myelogenous12 and other leukemias1314 indicating its potential use as a cancer chemotherapeutic and cancer preventive agent.…”
mentioning
confidence: 99%
“…In this study, EMT was evaluated under crocin treatment in vivo . For this aim, tumour growth of aggressive cancer cell lines (such as PC3 and 22rv1) was xenografted in nude mice treated by oral crocin . Results showed that the significant reduction in N‐cadherin and beta‐catenin expression and the increased expression of E‐cadherin led to EMT reversion …”
Section: Molecular Mechanisms Of Anticancer Effects Of Crocinmentioning
confidence: 99%
“…analysed the immunohistochemistry expression of proteases involved in the migratory and invasive properties of the mentioned xenografts after treatment with 0.4 m m crocin. Their results showed that crocin inhibits cell invasion through modulation of metalloproteinases and urokinase expression or activity …”
Section: Molecular Mechanisms Of Anticancer Effects Of Crocinmentioning
confidence: 99%